Equations of Unification: Mathematical Connections between Ramanujan's Recurring Numbers and Theoretical Cosmology (London Journal of Research In Science: Natural and Formal, 2025)
The search for a conceptual unity between the domains of discrete mathematics and continuous physics represents one of the deepest and most strategic challenges of modern science. Overcoming the dichotomy between the quantized world of numbers and the fluidity of spacetime is fundamental to develop a theoretical framework that can describe the universe in its entirety. The exploration of bridges between these two seemingly distant languages is not only an exercise in formal elegance, but a necessity to solve the enigmas that lie at the frontier of theoretical physics, from quantum gravity to the nature of the cosmological vacuum.This paper presents a further development of the Nardelli Master Equation, unveiling its profound mathematical and symbolic connections to Ramanujans Recurring Numbers. Through a multidisciplinary lens, we explore how this equation acts as a bridge between discrete number-theoretic phenomena and continuous geometric structures, revealing hidden symmetries across Geometric Measure Theory, Number Theory, Theoretical Cosmology, and String Theory. The recurrence patterns inspired by Ramanujan are shown to resonate with fractal geometries and cosmological constants, suggesting a unified framework where arithmetic intuition meets the fabric of spacetime. We propose that the Nardelli Master Equation, enriched by these connections, may serve not only as a tool for mathematical insight but also as a symbolic vessel for understanding the deep harmony between the microcosm of numbers and the macrocosm of the universe. This work invites further exploration into the structural unity of mathematics and physics thought.
Keywords: starch/xanthan proportion; reaction time; hydrophilic films characterization; Blockchain; Zero-Knowledge Proofs; Post-Quantum Cryptography; IoT Security; Privacy Preservation